Mechanical and morphological properties of polypropylene/nano α-Al2O3 composites - Mirjalili, Fatemeh; Abdullah, Luqman Chuah; Salahi, Esmail (Hindawi Publishing Corporation, 2014)
A nanocomposite containing polypropylene (PP) and nano α-Al2O3 particles was prepared using a Haake internal mixer. Mechanical tests, such as tensile and flexural tests, showed that mechanical properties of the composite were enhanced by addition of nano α-Al2O3 particles and dispersant agent to the polymer. Tensile strength was approximately 16% higher than pure PP by increasing the nano α-Al2O3 loading from 1 to 4 wt% into the PP matrix. The results of flexural analysis indicated that the maximum values of flexural strength and flexural modulus for nanocomposite without dispersant were 50.5 and 1954 MPa and for nanocomposite with dispersant were 55.88 MPa and 2818 MPa, respectively. However, higher concentration of nano α-Al2O3 loading resulted in reduction of those mechanical properties that could be due to agglomeration of nano α-Al2O3 particles. Transmission and scanning electron microscopic observations of the nanocomposites also showed that fracture surface became rougher by increasing the content of filler loading from 1 to 4% wt.